1992
DOI: 10.1093/oxfordjournals.aje.a116491
|View full text |Cite
|
Sign up to set email alerts
|

Joint Influence of Fat and Lean Body Composition Compartments on Femoral Bone Mineral Density in Premenopausal Women

Abstract: Body composition (fat and lean compartments) and bone mineral density were measured in 246 healthy premenopausal women, aged 20-40 years, residing in Tecumseh, Michigan. Body composition was measured using four-point bioelectrical impedance and values for fat and lean compartments categorized into tertiles. Additionally, each woman was classified into one of nine different cells based on her location within a 3 x 3 table which reflects the joint distribution of both fat and lean compartments. Bone mineral dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
0
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 0 publications
7
46
0
2
Order By: Relevance
“…The present finding that low body weight is a risk factor for low BMD is in agreement with studies in healthy individuals. [15][16][17][18] This is partly explained by a greater body size and bone size in heavier patients. Also, mechanical stress on bone is greater in obese than in lean individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The present finding that low body weight is a risk factor for low BMD is in agreement with studies in healthy individuals. [15][16][17][18] This is partly explained by a greater body size and bone size in heavier patients. Also, mechanical stress on bone is greater in obese than in lean individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight and fat and muscle components are also correlated with BD in humans [40,41] and mice [42]. Sowers et al [43] found that lean mass was associated with BD independent of fat mass, whereas fat mass was only associated with BD in the presence of high lean mass. In contrast, Reid et al [44] showed associations between BD and fat mass, but not lean mass.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple regression analysis revealed LBM and regional muscle mass to be a better predictor of bone mass (8,9). In either case, there has been a significant correlation between body composition and bone mass (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 96%
“…Bone mass has been demonstrated to be affected by body composition (4)(5)(6)(7)(8)(9)(10)(11)(12). Some investigators revealed body fat mass to be a good predictor of bone mass in subjects who are older, have a greater percentage of fat, and are physically inactive (5,10,11).…”
Section: Discussionmentioning
confidence: 99%